Governance Based on Cost Analysis: Unit Cost Analysis for Vocational Schools - Situmeang, C; Habibi, M R (KnE Social Sciences, 2018)
This study aims to calculate unit cost to produce one middle-level vocational school graduate (in Indonesian terms known as ‘Sekolah Menengah Kejuruan’ abbreviated as SMK). The calculation is required because operational grant funds (in Indonesian terms known as antuan Operational Sekolah abbreviated as BOS) are distributed so far to the same extent in all areas of Indonesia and for all majors. This is most likely less than optimal because in fact there are very basic characteristics differences including; Economic capacity of each region, the cost standard for each region, and the type of department in the school. Based on this, the researcher assumed that cost analysis should be done by considering these things as a basis to provide BOS funds tailored to specific characteristics. The data to be analyzed in this research is North Sumatra province data. This research is conducted in two stages, which in this report only completed the first phase which is a survey in North Sumatra region. Stages of survey to obtain data which then analyzed with related data such as community income, learning outcomes through the value of national examinations, tuition fee, and conditions of learning facilities. The research is funded by the ministries of research, technology and higher education through competing grant schemes for fiscal year 2017 and 2018. The result of correlation analysis between the variables shows that there is a strong relationship between the average income with average tuition paid by the community and between average tuition paid by the community with Quality Level of Education Facilities. The result of correlation analysis also shows a moderate relationship between the average tuition with learning outcomes measured through average national exam and relationship between quality level of education facilities with average national exam. While the relationship between average income with average national exam does not have a strong relationship. The result of correlation analysis concludes that further research is required to calculate unit cost. The results of these calculations can be used as a recommendation for policy makers to evaluate the funding system boss funds to pay attention to the characteristics as mentioned earlier. Keywords: component; vocational school; unit cost; unit analysis